1998
DOI: 10.2514/2.504
|View full text |Cite
|
Sign up to set email alerts
|

Passive Control of Supersonic Rectangular Jets via Nozzle Trailing-Edge Modifications

Abstract: A research program was carried out to explore the effects of nozzle trailing-edge modi cations on the ow structure, jet mixing with the ambient air, and jet noise of a rectangular supersonic jet. Nozzles with one modi ed trailing edge were used with the intention of enhancing mixing and reducing noise. The modi cations were simple cutouts in the plane of the nozzle wall and acted to induce large-scale streamwise vortices. A rectangular jet, with a design Mach number of 2 and with various trailing edges, was ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…Hysteresis in the aerodynamic coef cients for the computed solution can be observed for a lying between 17 and 19 deg. Qualitatively, these results look similar to those reported by Hoffman 1 for his experiments with the NACA 0015 airfoil for low FST.…”
supporting
confidence: 90%
“…Hysteresis in the aerodynamic coef cients for the computed solution can be observed for a lying between 17 and 19 deg. Qualitatively, these results look similar to those reported by Hoffman 1 for his experiments with the NACA 0015 airfoil for low FST.…”
supporting
confidence: 90%
“…Although the use of tabs is proved to be effective in enhancing mixing of supersonic jets, it results in thrust losses due to blockage effects of these vortex generators [6]. This motivated researchers to explore alternative techniques for generating streamwise vortices to enhance mixing [7][8][9][10][11][12][13][14][15]. Effects of nozzle trailing edge modifications on the flow structure and jet mixing with ambient air were explored by Samimy et al [7] and Kim and Samimy [8].…”
Section: Introductionmentioning
confidence: 99%
“…This motivated researchers to explore alternative techniques for generating streamwise vortices to enhance mixing [7][8][9][10][11][12][13][14][15]. Effects of nozzle trailing edge modifications on the flow structure and jet mixing with ambient air were explored by Samimy et al [7] and Kim and Samimy [8]. Their results indicated that in non-ideally expanded flow regimes, pairs of streamwise vortices of various strength and sign were generated and the mixing was significantly enhanced [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations